(untitled) (Geologica Macedonica, 2014)
The Ješevac volcanic complex located in central Serbia is made up of various Tertiary volcanic rocks. Kremenjača hill is situated on the SW rim of the Ješevac volcanic complex. Silica veins found in this site are made up of chalcedony varieties and crystalline quartz. Jasper veins are examined more thoroughly in this paper. Microscopic analysis has shown it is made up of cryptocrystalline silica with fluidal structure. X-ray powder diffraction analysis of the samples has shown crystalline silica-quartz, ruling out the presence of amorphous silica-opal. The results of spectrochemical analysis have indicated the presence of colouring agents originating mostly from ultramafic and mafic rocks. Key words: gemstone; silica veins; jasper; dacite